Volume 2 2004
DOI: 10.1115/esda2004-58253
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Earthquake Waves Based on Nonlinear Responses of RC Structures

Abstract: The calculation of the nonlinear time-response of structures such as RC (reinforced concrete) frames to base excitation such as earthquake waves is vital to ensure the safety of structures. Of course the response changes significantly with the applied base excitation. The usual approaches to compare the different earthquake waves are based on non-localized spectra, such as response spectra and power spectra, which do not contain any time information. However these non-localized spectra often do not explain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Research by Vlachos et al [11] suggested that, in the bimodal modified Kanai-Tajimi model, the spectrum strength factors, (1) 0 ( ) and (2) 0 ( ), have no direct relationship with the spectral energy of each mode; their values only represent linear combinations of the modes. Therefore, the following ratio is defined to replace the absolute values:…”
Section: Model Parameter Identification and Fittingmentioning
confidence: 99%
See 4 more Smart Citations
“…Research by Vlachos et al [11] suggested that, in the bimodal modified Kanai-Tajimi model, the spectrum strength factors, (1) 0 ( ) and (2) 0 ( ), have no direct relationship with the spectral energy of each mode; their values only represent linear combinations of the modes. Therefore, the following ratio is defined to replace the absolute values:…”
Section: Model Parameter Identification and Fittingmentioning
confidence: 99%
“…Among the identified parameters, (1) , (2) are defined as damping ratios of the top soil layer on the bedrock, which are normally constants. To simplify the analysis, the values of parameters (1) , (2) are set to the mean value of { (1) ( ), (2) ( )} identified at each time :…”
Section: Model Parameter Identification and Fittingmentioning
confidence: 99%
See 3 more Smart Citations